2015
DOI: 10.1007/s11186-015-9254-7
|View full text |Cite
|
Sign up to set email alerts
|

Global borderlands: a case study of the Subic Bay Freeport Zone, Philippines

Abstract: Abstract:By developing the concept of "global borderlands"-semi-autonomous, foreigncontrolled geographic locations geared toward international exchange-this article shifts the focus of globalization literature from elite global cities and cities on national borders to within-country sites owned and/or operated by foreigners and defined by significant social, cultural, and economic exchange. I analyze three shared features of these sites: semi-autonomy, symbolic and geographic boundaries, and unequal relations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The mean monthly family income of respondents was P46,348.71. [29,30,31] were parallel with the findings of the current study regarding the significant association between the learners and lower monthly family incomes in Zambales. Specifically, the findings indicated that the majority of the participants came from families with a monthly income of P19,999 and below.…”
Section: Resultssupporting
confidence: 87%
“…The mean monthly family income of respondents was P46,348.71. [29,30,31] were parallel with the findings of the current study regarding the significant association between the learners and lower monthly family incomes in Zambales. Specifically, the findings indicated that the majority of the participants came from families with a monthly income of P19,999 and below.…”
Section: Resultssupporting
confidence: 87%
“…Contemporary ethnographers also follow this pattern (Young Jr, 2004; Small, 2004; Venkatesh, 2002; Wherry, 2011; Anderson, 2011; Khan, 2010; Reyes, 2015). For example, Jane Jacobs (1992 [1961]) names Greenwich Village as the location in which she argues that neighborhood safety can be reproduced, in part, by maintaining ‘eyes upon the street’ (p. 35) – that is, when those invested in the neighborhood keep watch of people’s comings and goings.…”
Section: Naming Placesmentioning
confidence: 92%
“…Because I shared this information, I will likely include this information in my current writings about Subic Bay as I reflect on the methodological and theoretical importance of changing field sites. As such, others can hypothesize and/or investigate how and why dynamics between these two differ and what that means for foreign–local encounters in global borderlands (Reyes, 2015).…”
Section: Sharing Datamentioning
confidence: 99%
“…Instead of the traditional approach to focus on a group of people (e.g. Anderson, 1990;Liebow, 2003Liebow, [1967), I focused on how different types of people navigate a space that is transient and semi-autonomous -what elsewhere is called a global borderland (Reyes, 2015;Reyes, forthcoming). As such, I was continually moving between different groups of people and observing different spaces and places that people occupied within the zone.…”
Section: Ethnographic Toolkitmentioning
confidence: 99%